Forest avifauna of Universiti Kebangsaan Malaysia and some other forest remnants in Selangor, Peninsular Malaysia [Malaysia] - Ford, H.A. (New England Univ., Armidale NSW 2351 (Australia). Dept. of Zoology) (2013)
Birds were surveyed in three large forest remnants (550-830 ha) and surrounding open habitats in Selangor. A total of 169 species were detected, though 64 of these regularly occur in more open or modified habitat. One hundred and five species are forest-dependent, compared with about 260 species in lowland forest generally in Peninsular Malaysia and 208 forest-dependent species recorded in a long-term study in continuous lowland rainforest. Patches are depauperate in phasianids, trogons, hornbills, thrushes, flycatchers and babblers. Most of these birds occur in the lower storey of forest, so extensive areas of rainforest are needed to conserve them. Cuckoos, woodpeckers, bulbuls, sunbirds and the cuckoo-shrike guild are well-represented in patches. Many of these species are found in the canopy or on the edges of the forest. Rainforest remnants therefore have considerable value for research, education, recreation and conservation, because so much of the forest has been removed for agriculture or urban expansion in lowland Malaysia. However, the experience in Singapore and Bogor Botanical gardens, where numerous species have gone extinct, suggests that the patches in Selangor should be kept as large as possible and may require active management to retain their current richness. Neglect, or further attrition, as is currently happening to them could lead to a steep decline in their avian diversity